Wiley-Blackwell encyclopedia of human evolution - Wood, Bernard A.; Wiley InterScience (Online service) (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2011)
"This comprehensive A to Z encyclopedia provides extensive coverage of important scientific terms related to improving our understanding of how we evolved. Specifically, the 5,000 entries cover evidence and methods used to investigate the relationships among the living great apes, evidence about what makes the behavior of modern humans distinctive, and evidence about the evolutionary history of that distinctiveness, as well as information about modern methods used to trace the recent evolutionary history of modern human populations. This text provides a resource for everyone studying the emergence of Homo sapiens"--
"The long-term plan for the Wiley-Blackwell Encyclopedia of Human Evolution (W-BEHE) is that it will be an authoritative and accessible source of information about the hominin clade of the tree of life. Entries cover: - general evolutionary principles, - information about the molecular and developmental biological approaches used to help understand the pattern and process of evolution, - methods used to investigate relationships among the living great apes and modern humans, - methods germane to understanding the origins and evolutionary history of the hominin clade and its climatic and ecological context, - what makes the behavior of modern humans distinctive and the evolutionary history of that distinctiveness, - information about the modern methods used to capture and interpret data from the hominin fossil and archeological records, as well as comparative biology, - nonhominin fossil evidence germane to the evolution of the hominin clade, - specialist terms used to describe the hominin fossil and archeological records, - hypotheses germane to interpreting human evolutionary history, - biographies of individuals who have made significant contributions to the accumulation of the fossil and archeological, and other, evidence and to its interpretation, - institutions and organizations that have contributed to our understanding of human evolutionary history, - information about hominin fossil and comparative great ape collections and about some of the repositories that hold hominin fossil collections"--
Front Matter -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z -- References.
Includes bibliographical references.
Print version record.
Keywords: Human evolution -- Encyclopedias; SCIENCE -- Life Sciences -- Evolution; Human evolution; Electronic books; Encyclopedias